Discrimination of beef production system and regional geography by multivariate analysis of stable isotope ratios (C, N, S, O, H) - Hannah Whyte; Raquel Cama-Moncunill; Peter G. Dunne; Aidan P. Moloney; Frank McDermott; Matta Ebaid; Michael Salter-Townshend; Frank J. Monahan; Olaf Schmidt (Food Control, 2026)

Behavioural responses to heat in an arid-zone bird vary with thermal, hygric and social factors - J. R. D. Whyte; A. E. McKechnie; J. K. Crossley; S. J. Cunningham (Oecologia, 2026)
The severity of fitness costs resulting from behavioural trade-offs between heat dissipation and activities such as foraging is increasing with advancing climate change. In terrestrial habitats, shade and water may buffer individuals from the negative effects of heat exposure, as may load-lightening in group-living species. We tested the hypothesis that thermal and hygric properties of home ranges (shade and water availability) and social factors (group size) influence the costs associated with hot weather, using a population of white-browed sparrow-weavers ( Plocepasser mahali ) in the southern Kalahari Desert. Across all sparrow-weaver groups, heat avoidance (shade-seeking) and dissipation (panting) behaviours increased with increasing air temperature ( T air ), whereas foraging declined. Birds occupying shadier home ranges delayed the onset of panting to higher T air and foraged less while maintaining overall peck rates. Birds with access to water foraged more, maintained higher peck rates and sought shade at higher T air compared to birds without. However, they did not pant more, making the mechanism underpinning their increased foraging effort unclear. Birds in larger groups both panted more overall and sought shade at lower T air than birds in smaller groups but maintained similar overall peck rates. Taken together, these results suggest birds in shadier home ranges can forage more efficiently, buffering foraging costs at high T air . Our data therefore suggest that some impacts of increasing T air under climate change can be buffered by shade availability, but the impacts of water availability and social factors are less clear.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

The potential of the mineral composition to discriminate between beef from different cattle diets and between individual muscles - Hannah Whyte; Raquel Cama-Moncunill; Peter G. Dunne; Cormac McElhinney; Frank J. Monahan; Olaf Schmidt; Aidan P. Moloney (Food Control, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

The COSPAR planetary protection policy for missions to Icy Worlds: A review of history, current scientific knowledge, and future directions - P.T. Doran; A. Hayes; O. Grasset; A. Coustenis; O. Prieto-Ballesteros; N. Hedman; O. Al Shehhi; E. Ammannito; M. Fujimoto; F. Groen; J.E. Moores; C. Mustin; et al. (Life Sciences in Space Research, 2024)

Comparison of the impact of UV-light emitting diode and UV lamp at pilot-plant scale level on quality parameters and consumer perception of fresh chicken meat - Arturo B. Soro; Cristina Botinestean; Sajad Shokri; Alexandre Juge; Shay Hannon; Paul Whyte; Declan J. Bolton; Paula Bourke; Mahesha M. Poojary; Brijesh K. Tiwari (Food Chemistry, 2024)

The efficiency of UV light-emitting diodes (UV-LED) in decontaminating Campylobacter and Salmonella and natural microbiota in chicken breast, compared to a UV pilot-plant scale device - Arturo B. Soro; Daniel Ekhlas; Sajad Shokri; Ming Ming Yem; Rui Chao Li; Soukaina Barroug; Shay Hannon; Paul Whyte; Declan J. Bolton; Catherine M. Burgess; Paula Bourke; Brijesh K. Tiwari (Food Microbiology, 2023)

Brain metabolite levels in remitted psychotic depression with consideration of effects of antipsychotic medication - Hideaki Tani; Iska Moxon-Emre; Natalie J. Forde; Nicholas H. Neufeld; Kathleen S. Bingham; Ellen M. Whyte; Barnett S. Meyers; George S. Alexopoulos; Matthew J. Hoptman; Anthony J. Rothschild; Hiroyuki Uchida; Alastair J. Flint; et al. (Brain Imaging and Behavior, 2023)
Background The neurobiology of psychotic depression is not well understood and can be confounded by antipsychotics. Magnetic resonance spectroscopy (MRS) is an ideal tool to measure brain metabolites non-invasively. We cross-sectionally assessed brain metabolites in patients with remitted psychotic depression and controls. We also longitudinally assessed the effects of olanzapine versus placebo on brain metabolites. Methods Following remission, patients with psychotic depression were randomized to continue sertraline + olanzapine ( n = 15) or switched to sertraline + placebo ( n = 18), at which point they completed an MRS scan. Patients completed a second scan either 36 weeks later, relapse, or discontinuation. Where water-scaled metabolite levels were obtained and a Point-RESolved Spectroscopy sequence was utilized, choline, myo-inositol, glutamate + glutamine (Glx), N -acetylaspartate, and creatine were measured in the left dorsolateral prefrontal cortex (L-DLPFC) and dorsal anterior cingulate cortex (dACC). An ANCOVA was used to compare metabolites between patients ( n = 40) and controls ( n = 46). A linear mixed-model was used to compare olanzapine versus placebo groups. Results Cross-sectionally, patients (compared to controls) had higher myo-inositol (standardized mean difference [SMD] = 0.84; 95%CI = 0.25–1.44; p = 0.005) in the dACC but not different Glx, choline, N -acetylaspartate, and creatine. Longitudinally, patients randomized to placebo (compared to olanzapine) showed a significantly greater change with a reduction of creatine (SMD = 1.51; 95%CI = 0.71–2.31; p = 0.0002) in the dACC but not glutamate + glutamine, choline, myo-inositol, and N -acetylaspartate. Conclusions Patients with remitted psychotic depression have higher myo-inositol than controls. Olanzapine may maintain creatine levels. Future studies are needed to further disentangle the mechanisms of action of olanzapine.

Current challenges in the application of the UV-LED technology for food decontamination - Arturo B. Soro; Sajad Shokri; Iolanda Nicolau-Lapeña; Daniel Ekhlas; Catherine M. Burgess; Paul Whyte; Declan J. Bolton; Paula Bourke; Brijesh K. Tiwari (Trends in Food Science & Technology, 2023)

Correction to: Description of nest architecture and ecological notes on the bumblebee Bombus (Pyrobombus) lapponicus (Hymenoptera: Apidae: Bombini) - B. Martinet; K. Przybyla; J. Atkins; Y. Bosiger; D. Evrard; P. Gill; J. van Alphen; G. Whyte; P. Rasmont (Insectes Sociaux, 2022)

Description of nest architecture and ecological notes on the bumblebee Bombus (Pyrobombus) lapponicus (Hymenoptera: Apidae: Bombini) - B. Martinet; K. Przybyla; J. Atkins; Y. Bosiger; D. Evrard; P. Gill; J. van Alphen; G. Whyte; P. Rasmont (Insectes Sociaux, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Thiomicrorhabdus streamers and sulfur cycling in perennial hypersaline cold springs in the Canadian high Arctic - Elisse Magnuson; Nadia C.S. Mykytczuk; Andre Pellerin; Jacqueline Goordial; Susan M. Twine; Boswell Wing; Simon J. Foote; Kelly Fulton; Lyle G. Whyte (Environmental Microbiology, 2021)
Summary The Gypsum Hill (GH) springs on Axel Heiberg Island in the Canadian high Arctic are host to chemolithoautotrophic, sulfur‐oxidizing streamers that flourish in the high Arctic winter in water temperatures from −1.3 to 7°C with ~8% salinity in a high Arctic winter environment with air temperatures commonly less than −40°C and an average annual air temperature of −15°C. Metagenome sequencing and binning of streamer samples produced a 96% complete Thiomicrorhabdus sp. metagenome‐assembled genome representing a possible new species or subspecies. This is the most cold‐ and salt‐extreme source environment for a Thiomicrorhabdus genome yet described. Metaproteomic and metatranscriptomic analysis attributed nearly all gene expression in the streamers to the Thiomicrorhabdus sp. and suggested that it is active in CO 2 fixation and oxidation of sulfide to elemental sulfur. In situ geochemical and isotopic analyses of the fractionation of multiple sulfur isotopes determined the biogeochemical transformation of sulfur from its source in Carboniferous evaporites to biotic processes occurring in the sediment and streamers. These complementary molecular tools provided a functional link between the geochemical substrates and the collective traits and activity that define the microbial community's interactions within a unique polar saline habitat where Thiomicrorhabdus ‐dominated streamers form and flourish.

Genetic diversity of provitamin-A cassava (Manihot esculenta Crantz) in Sierra Leone - I. Kamanda; E. T. Blay; I. K. Asante; A. Danquah; B. E. Ifie; E. Parkes; P. Kulakow; I. Rabbi; A. Conteh; J. S. Kamara; H. K. Mensah; J. B. A. Whyte; et al. (Genetic Resources and Crop Evolution, 2020)
Understanding the genetic diversity among accessions and germplasm is an important requirement for crop development as it allows for the selection of diverse parental combinations for enhancing genetic gain in varietal selection, advancement and release. The study aimed to characterize 183 provitamin A cassava ( Manihot esculenta Crantz) accessions and five Sierra Leonean varieties using morphological traits, total carotenoid content and SNP markers to develop a collection for conservation and further use in the cassava breeding program. Both morphological parameters and 5634 SNP markers were used to assess the diversity among the provitamin-A cassava accessions and varieties. Significant differences were observed among the accessions for most of the traits measured. The first five PCs together accounted for 70.44% of the total phenotypic variation based on yield and yield components among the 183 provitamin-A cassava accessions and five Sierra Leonean varieties. The present study showed that provitamin-A cassava accessions in Sierra Leone have moderate to high diversity based on morphological and molecular assessment studies. The similarity index among the 187 and 185 cassava accessions grouped them into 6 and 9 distinct clusters based on morphological and molecular analyses, respectively. A significant positive, but low correlation ( r = 0.104; p < 0.034), was observed between the two dendrograms. The results obtained will serve as a guide and basis of germplasm management and improvement for total carotenoid content, yield and African cassava mosaic disease resistance in Sierra Leone.

Impact of co‐infection with Lepeophtheirus salmonis and Moritella viscosa on inflammatory and immune responses of Atlantic salmon ( Salmo salar ) - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)
This study was conducted to determine the effects of a co‐infection with Moritella viscosa at different exposure levels of sea lice Lepeophtheirus salmonis in Atlantic salmon ( Salmo salar ). M. viscosa (1.14 × 10 6 cfu/ml) was introduced to all experimental tanks at 10 days post‐lice infection (dpLs). Mean lice counts decreased over time in both the medium lice co‐infection (31.5 ± 19.0 at 7 dpLs; 16.9 ± 9.3 at 46 dpLs) and high lice co‐infection (62.0 ± 10.8 at 7 dpLs; 37.6 ± 11.3 at 46 dpLs). There were significantly higher mortalities and more severe skin lesions in the high lice co‐infected group compared to medium lice co‐infected group or M. viscosa ‐only infection. Quantitative gene expression analysis detected a significant upregulation of genes in skin from the high lice co‐infection group consistent with severe inflammation ( il‐8 , mmp‐9 , hep, saa ). Skin lesions retrieved throughout the study were positive for M. viscosa growth, but these were rarely located in regions associated with lice. These results suggest that while M. viscosa infection itself may induce skin lesion development in salmon, co‐infection with high numbers of lice can enhance this impact and significantly reduce the ability of these lesions to resolve, resulting in increased mortality.

Cover Image - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)

High Degree of Genetic Heterogeneity for Hereditary Cerebellar Ataxias in Australia - Ce Kang; Christina Liang; Kate E. Ahmad; Yufan Gu; Sue-Faye Siow; James G. Colebatch; Scott Whyte; Karl Ng; Philip D. Cremer; Alastair J. Corbett; Ryan L. Davis; Tony Roscioli; et al. (The Cerebellum, 2019)

Desiccation Resistance and Micro-Climate Adaptation: Cuticular Hydrocarbon Signatures of Different Argentine Ant Supercolonies Across California - Jan Buellesbach; Brian A. Whyte; Elizabeth Cash; Joshua D. Gibson; Kelsey J. Scheckel; Rebecca Sandidge; Neil D. Tsutsui (Journal of Chemical Ecology, 2018)

Towards Alternative Approaches for Coupling of a Soft Robotic Sleeve to the Heart - Markus A. Horvath; Claudia E. Varela; Eimear B. Dolan; William Whyte; David S. Monahan; Christopher J. Payne; Isaac A. Wamala; Nikolay V. Vasilyev; Frank A. Pigula; David J. Mooney; Conor J. Walsh; Garry P. Duffy; et al. (Annals of Biomedical Engineering, 2018)

Current knowledge and breeding perspectives for the spider plant (Cleome gynandra L.): a potential for enhanced breeding of the plant in Africa - A. O. Kwarteng; J. Abogoom; R. Adu Amoah; D. Nyadanu; T. Ghunney; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; D. D. Asiedu; T. Whyte (Genetic Resources and Crop Evolution, 2018)

Current knowledge and breeding avenues to improve upon Frafra potato (Solenostemon rotundifolius (Poir.) J. K. Morton) - A. O. Kwarteng; T. Ghunney; R. Adu Amoah; D. Nyadanu; J. Abogoom; K. C. Nyam; J. Z. Ziyaaba; E. O. Danso; T. Whyte; D. D. Asiedu (Genetic Resources and Crop Evolution, 2018)

Microscopic characterization of the bacterial cell envelope of Planococcus halocryophilus Or1 during subzero growth at −15 °C - N. C. S. Mykytczuk; J. R. Lawrence; C. R. Omelon; G. Southam; L. G. Whyte (Polar Biology, 2016)

Ventricular structure, function, and focal fibrosis in anabolic steroid users: a CMR study - Peter J. Angell; Tevfik F. Ismail; Andrew Jabbour; Gillian Smith; Annette Dahl; Ricardo Wage; Greg Whyte; Daniel J. Green; Sanjay Prasad; Keith George (European Journal of Applied Physiology, 2014)

A fixed‐dose approach to conducting emamectin benzoate tolerance assessments on field‐collected sea lice, Lepeophtheirus salmonis - S K Whyte; J D Westcott; A Elmoslemany; K L Hammell; C W Revie (Journal of Fish Diseases, 2013)
In N ew B runswick, C anada, the sea louse, L epeophtheirus salmonis, poses an on‐going management challenge to the health and productivity of commercially cultured A tlantic salmon, S almo salar . While the in‐feed medication, emamectin benzoate ( SLICE ® ; M erck), has been highly effective for many years, evidence of increased tolerance has been observed in the field since late 2008. Although bioassays on motile stages are a common tool to monitor sea lice sensitivity to emamectin benzoate in field‐collected sea lice, they require the collection of large numbers of sea lice due to inherent natural variability in the gender and stage response to chemotherapeutants. In addition, sensitive instruments such as EC 50 analysis may be unnecessarily complex to characterize susceptibility subsequent to a significant observed decline in efficacy. This study proposes an adaptation of the traditional, dose–response format bioassay to a fixed‐dose method. Analysis of 657 bioassays on preadult and adult stages of sea lice over the period 2008–2011 indicated a population of sea lice in N ew B runswick with varying degrees of susceptibility to emamectin benzoate. A seasonal and spatial effect was observed in the robustness of genders and stages of sea lice, which suggest that mixing different genders and stages of lice within a single bioassay may result in pertinent information being overlooked. Poor survival of adult female lice in bioassays, particularly during M ay/ J une, indicates it may be prudent to consider excluding this stage from bioassays conducted at certain times of the year. This work demonstrates that fixed‐dose bioassays can be a valuable technique in detecting reduced sensitivity in sea lice populations with varying degrees of susceptibility to emamectin benzoate treatments.

Vascular endothelium-specific overexpression of human catalase in cloned pigs - J. J. Whyte; M. Samuel; E. Mahan; J. Padilla; G. H. Simmons; A. A. Arce-Esquivel; S. B. Bender; K. M. Whitworth; Y. H. Hao; C. N. Murphy; E. M. Walters; R. S. Prather; et al. (Transgenic Research, 2011)

Combined carbohydrate–protein supplementation improves competitive endurance exercise performance in the heat - Andrew J. Cathcart; Scott R. Murgatroyd; Alison McNab; Laura J. Whyte; Chris Easton (European Journal of Applied Physiology, 2011)

Optimization of square-wave electroporation for transfection of porcine fetal fibroblasts - Jason W. Ross; Jeffrey J. Whyte; Jianguo Zhao; Melissa Samuel; Kevin D. Wells; Randall S. Prather (Transgenic Research, 2010)

Diastolic function in healthy humans: non-invasive assessment and the impact of acute and chronic exercise - Keith P. George; Louise H. Naylor; Greg P. Whyte; Rob E. Shave; David Oxborough; Daniel J. Green (European Journal of Applied Physiology, 2010)

Quantitative linkage genome scan for atopy in a large collection of Caucasian families - Bradley T. Webb; Edwin van den Oord; Anthony Akkari; Steve Wilton; Tina Ly; Rachael Duff; Kathleen C. Barnes; Karin Carlsen; Jorrit Gerritsen; Warren Lenney; Michael Silverman; Peter Sly; et al. (Human Genetics, 2007)

The effects of marathon running on expression of the complement regulatory proteins CD55 (DAF) and CD59 (MACIF) on red blood cells - Richard J. Simpson; Geraint D. Florida-James; Greg P. Whyte; Natalie Middleton; Rob Shave; Keith George; Keith Guy (European Journal of Applied Physiology, 2006)

The effects of intensive, moderate and downhill treadmill running on human blood lymphocytes expressing the adhesion/activation molecules CD54 (ICAM-1), CD18 (β2 integrin) and CD53 - Richard J. Simpson; Geraint D. Florida-James; Greg P. Whyte; Keith Guy (European Journal of Applied Physiology, 2006)

Characterization of lymphocytic infiltrates in progressive multifocal leukoencephalopathy: Co-localization of CD8 + T cells with JCV-infected glial cells - Christian Wüthrich; Santosh Kesari; Woong-Ki Kim; Kenneth Williams; Rebecca Gelman; Derek Elmeric; Umberto De Girolami; Jeffrey T Joseph; Tessa Hedley-Whyte; Igor J Koralnik (Journal of NeuroVirology, 2006)

New sources of resistance to Radopholus similis in Musa germplasm from Asia - C. Dochez; J. Dusabe; J. Whyte; A. Tenkouano; R. Ortiz; D. De Waele (Australasian Plant Pathology, 2006)

The Effect of Creosote on Vitellogenin Production in Rainbow Trout (Oncorhynchus mykiss) - J. P. Sherry; J. J. Whyte; N. A. Karrow; A. Gamble; H. J. Boerman; N. C. Bol; D. G. Dixon; K. R. Solomon (Archives of Environmental Contamination and Toxicology, 2006)

First record of Mycosphaerella heimii in Australia - G. Whyte; T. I. Burgess; P. A. Barber; G. E. St J. Hardy (Australasian Plant Pathology, 2005)

Effect of Maintaining Rainbow Trout in Creosote Microcosms on Lens Optical Properties and Liver 7-Ethoxyresorufin- O -Deethylase (EROD) Activity - J. J. Whyte; K. L. Herbert; N. A. Karrow; D. G. Dixon; J. G. Sivak; N. C. Bols (Archives of Environmental Contamination and Toxicology, 2000)

Characterization of a murine cytomegalovirus-induced immunosuppressive factor - P. F. Whyte; R. Subramaniam; J. B. Hudson (Archives of Virology, 1987)